Thucydides : An Introduction for the Common Reader - Zagorin, Perez (Book collections on Project MUSE., 2009)
This book is a concise, readable introduction to the Greek author Thucydides, who is widely regarded as one of the foremost historians of all time. Why does Thucydides continue to matter today? Perez Zagorin answers this question by examining Thucydides' landmark History of the Peloponnesian War, one of the great classics of Western civilization. This history, Zagorin explains, is far more than a mere chronicle of the conflict between Athens and Sparta, the two superpowers of Greece in the fifth century BCE. It is also a remarkable story of politics, decision-making, the uses of power, and the.